2005
DOI: 10.3168/jds.s0022-0302(05)73126-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Garlic Oil and Four of its Compounds on Rumen Microbial Fermentation

Abstract: Different concentrations (3, 30, 300, and 3000 mg/L of culture fluid) of garlic oil (GAR), diallyl sulfide (DAS), diallyl disulfide (DAD), allicin (ALL), and allyl mercaptan (ALM) were incubated for 24 h in diluted ruminal fluid with a 50:50 forage:concentrate diet (17.7% crude protein; 30.7% neutral detergent fiber) to evaluate their effects on rumen microbial fermentation. Garlic oil (30 and 300 mg/L), DAD (30 and 300 mg/L), and ALM (300 mg/L) resulted in lower molar proportion of acetate and higher proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
228
9
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(281 citation statements)
references
References 27 publications
31
228
9
13
Order By: Relevance
“…This was also observed for the gas production rate and might suggest that at that level of dosage the fermentation was not compromised. Indeed, the DNDF was only significantly affected by CAR and PTS with a reduction of 28% in both cases, which is consistent with values reported using other garlic compounds and essential oils in vitro (Busquet et al, 2005). Although a possible overestimation of the in vitro method to estimate digestibility based on NDF residue has been reported (Getachew et al, 2004), this method is accepted for comparative purposes; nevertheless, these results need to be confirmed in vivo in producing animals with faster passing digesta rates than the 72 h used in this in vitro assay.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…This was also observed for the gas production rate and might suggest that at that level of dosage the fermentation was not compromised. Indeed, the DNDF was only significantly affected by CAR and PTS with a reduction of 28% in both cases, which is consistent with values reported using other garlic compounds and essential oils in vitro (Busquet et al, 2005). Although a possible overestimation of the in vitro method to estimate digestibility based on NDF residue has been reported (Getachew et al, 2004), this method is accepted for comparative purposes; nevertheless, these results need to be confirmed in vivo in producing animals with faster passing digesta rates than the 72 h used in this in vitro assay.…”
supporting
confidence: 78%
“…Animals were cared for by trained personnel in accordance with the Spanish guidelines for experimental animal protection (Royal Decree No. 1201/2005 and the European Convention for the Protection of Vertebrates used for Experimental and other Scientific Purposes (European Directive 86/609). All the experimental procedures involved in this study were approved by the Animal Welfare Committee at the Institute of Animal Nutrition (CSIC, Spain).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bergman [17] estimated that 27% to 55% of the glucose metabolized by ruminants originates from propionate (as an energy precursor). Previous studies documented the lower acetate, the greater propionate and butyrate proportions and resulting lower acetate to propionate ratio in garlic supplemented diet suggested that garlic constituents might help to improve the efficiency of energy utilization in the rumen [3,4,18] . This may explain to some extent how garlic can improve serum glucose concentration.…”
Section: Discussionmentioning
confidence: 99%
“…defaunation, decreased methane production, decreased ruminal degradation of dietary proteins, reducing the proportion of acetate and increasing that of propionate) and consequently on animal production and performances [2][3][4][5] . The hypothesis addressed in this paper was that dietary addition of raw garlic would lead to efficacy of food utilization and improving in energy related blood metabolites, which would be reflected by increases in milk production and changes in milk composition.…”
Section: Introductionmentioning
confidence: 99%